Kulturowy wymiar ceremoniału wojskowego - Nowakowska, Marta; Świderski, Krzysztof (Wydział Nauk Historycznych i Pedagogicznych Uniwersytetu Wrocławskiego, Katedra Etnologii i Antropologii Kulturowej, 2018)
The goal of this article is to present individual forms and stages of military ceremonies in the historical and modern context. It emphasizes the constancy of structures which, despite the ongoing processes of globalization, are preserved untouched for many centuries. The authors refer to the ideas of traditional ritualsand ceremonies, trying to address the problem to anthropological theory.